Perfil etiológico da mastite bovina na bacia leiteira do oeste paranaense, Brasil - Jardim, Júlia Gazzoni; Deminicis, Bruno Borges; Peixoto, Erika Cosendey Toledo de Mello; Heinzen, Eduardo Luiz; Domingues, Paulo Francisco [UNESP] (My University, 2014)
The aim of this study was evaluate the occurrence, infectious etiology and risk factors associated with mastitis in 331 dairy cows from sixteen farms located in the region of Marechal Cândido Rondon in the State of Paraná, Brazil. Both cows as the properties were selected of a non-random form and being selected 20% of lactation cows from each farm. The test for identification of subclinical mastitis was the California Mastitis Test and the diagnosis of the clinical mastitis was carried out by the observation of signs of inflammation in the udder and macroscopic changes in milk. Of lactating cows, 195 (60.77%) were positive for mastitis and 93,75% of the farms analyzed had at least one positive animal. The etiologic agents isolated in a total of three hundred twenty-nine samples were Staphylococcus aureus (47.2%), Staphylococcus sp. (29.2%), Streptococcus dysgalactiae (18.1%), Streptococcus uberis (16,7%), Corynebaterium spp. (11,1%) and Streptococcus intermedius (1.39%). Besides, was evaluated the interaction of the type of mechanical milking in function of the mastitis degree and the use of the disinfection of teats before and after milking was not interference in mastitis incidence, however, the accomplishment of the disinfection of teats before and after -dipping favored in the control of subclinical mastitis. We conclude that the significant occurrence of mastitis in herds is due to improper management conditions. The adoption of good management and prophylactic measures, assisted by a professional of Animal Science surgeon will allow the reduction of this disease in herds.

O objetivo neste estudo foi avaliar a ocorrência, etiologia infecciosa e os fatores de risco associados à mastite em 331 vacas, provenientes de 16 propriedades leiteiras localizadas na região de Marechal Cândido Rondon, PR. Tanto as vacas quanto as propriedades foram selecionados de forma não aleatória e foram escolhidas 20% das vacas em lactação de cada propriedade. O teste para identificação da mastite subclínica foi o California Mastitis Test e o diagnóstico da mastite clínica foi realizado pela observação de sinais de inflamação no úbere e alterações macroscópicas no leite. Das vacas em lactação, 195 (60,77%) estavam com mastite e 93,75% das propriedades analisadas tinham pelo menos um animal positivo. Os agentes etioló- gicos isolados em um total de 329 amostras de leite foram Staphylococcus aureus (47,2%), Staphylococcus sp. (29,2%), Streptococcus dysgalactiae (18,1%), Streptococcus uberis (16,7%), Corynebaterium spp. (11,1%) e Streptococcus intermedius (1,39%). Além disso, avaliou-se a interação do tipo de ordenhadeira em função do grau de mastite e o uso de desinfecção de tetos antes e após ordenha não sendo verificada interferência na incidência de mastite, entretanto, a prática de desinfecção dos tetos antes e após a ordenha, favoreceu o controle de mastite subclínica. Conclui-se que a ocorrência de mastite deve-se a condições de manejo inadequadas. A adoção de boas práticas de manejo e medidas profiláticas, assistidas por um Zootecnista permitirá a diminuição dessa enfermidade nos rebanhos.
Etiological profile of bovine mastitis from dairy farms in the Western Paraná, Brazil
Keywords: Disinfection; Mastitis; Quality of milk; Desinfecção; Mastite; Qualidade do leite